Commutators-based graph in polygroup - Mohammad Hamidi; Elahe Mohammadzadeh; Somayeh Amirmofidi (Journal of Mahani Mathematical Research)
In this paper, first, we study commutators of a polygroup. Then for a finite polygroup $P$ and a fixed element $g \in P$, we introduce the $g$-graph $Δ_P^g$. In addition, with some additional conditions, we see that it is connected and the diameter is at most $3$. Then, we investigate isomorphic graphs. Specially, we obtain a new isomorphic graph derived from an isomorphic graph and two non-commutative isomorphic polygroups. Also, we show that two polygroups with isomorphic graphs preserve nilpotency.